1995
DOI: 10.1590/s0074-02761995000100022
|View full text |Cite
|
Sign up to set email alerts
|

Integrated control measures against Culex quinquefasciatus, the vector of filariasis in Recife

Abstract: Integrated control measures against Culex quinquefasciastus have been implemented in a pilot urban area in Recife, Brazil. About 3,000 breeding sites found within the operational area were responsible for very high mosquito densities recorded during the pretrial period. Physical control measures have been applied to cess pits before starting a series of 37 treatments of the other sites with Bacillus sphaericus strain 2362, over 27 months. In spite of the difficulties due to environmental conditions, very signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 0 publications
1
34
0
7
Order By: Relevance
“…In equatorial-tropical regions, the species is reported as the primary vector of Wuchereria bancrofti in the transmission cycle of lymphatic filariasis 36 . In subtropical and temperate urban areas, it is implicated as the primary vector of West Nile Virus 23 and other arboviruses 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In equatorial-tropical regions, the species is reported as the primary vector of Wuchereria bancrofti in the transmission cycle of lymphatic filariasis 36 . In subtropical and temperate urban areas, it is implicated as the primary vector of West Nile Virus 23 and other arboviruses 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Yet Orlova et al (21) demonstrated that crystalliferous strains of B. laterosporus presented LC 50 values similar to those attained with Bacillus thuringiensis serovar israelensis in bioassays employing larvae of three species of mosquitoes, with the larvicidal activity of B. laterosporus being associated with spores and crystalline inclusions. Although Bacillus thuringiensis and Bacillus sphaericus have been used as biological control agents in many countries (4,18,23,24), some strains still present problems, including low environmental persistence and a restricted range of targets. Thus, the availability of alternative agents would be highly desirable.…”
mentioning
confidence: 99%
“…and Anopheles sp. larvae, showing specific efficacy and feasibility as an effective tool for controlling vector populations (Karch et al, 1992;Kumar et al, 1994Kumar et al, , 1996Regis et al, 1994). B. sphuericus displays high toxicity against Cu1e.x pipiens and variable toxicity levels against Anopheles and Aedes, according to the species and to the bacterial strain.…”
mentioning
confidence: 99%